2015
DOI: 10.1002/app.42937
|View full text |Cite
|
Sign up to set email alerts
|

Microwave‐assisted green approach for graft copolymerization of l‐lactic acid onto starch

Abstract: Poly L-lactic acid grafted starch (St-g-PLA) copolymers were directly synthesized under microwave irradiation by using sodium hydroxide (NaOH) and stannous 2-ethyl hexanoate acting as a catalyst, without the use of toxic solvents. The product were characterized by Fourier transform infrared spectroscopy (FTIR), nuclear magnetic resonance ( 13 C CP/MAS NMR), X-ray diffraction (XRD), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA-DTG). SEM analysis indicated that microwave heating had a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 52 publications
1
11
0
Order By: Relevance
“…These results indicated the semi‐crystalline nature of corn starch had changed into amorphous character after grafting with caffeic acid. The elimination of starch crystalline peaks in caffeic acid‐g‐starch was mainly due to the fact that the original starch granules were broken down during gelatinization . In addition, the intermolecular hydrogen bonding of starch might be greatly destroyed during grafting processes.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicated the semi‐crystalline nature of corn starch had changed into amorphous character after grafting with caffeic acid. The elimination of starch crystalline peaks in caffeic acid‐g‐starch was mainly due to the fact that the original starch granules were broken down during gelatinization . In addition, the intermolecular hydrogen bonding of starch might be greatly destroyed during grafting processes.…”
Section: Resultsmentioning
confidence: 99%
“…The appearance of two peaks at 1228 and 2994 cm −1 , which were due to the OH bending and CH aliphatic groups of the PLA fragment compared to starch, strongly showed that the grafting of the PLA chains onto starch was successfully carried out through the application of shear‐mixing and reactive‐extrusion methods [Figure (a)]. The grafted PLA molar fraction in the St‐ g ‐PLA copolymers was calculated with the absorption bands of starch (1227 cm −1 for St CH 2 peak) and LA units [1736 cm −1 for LA CO ester peak; Figure (a)] . It was clear that with the application of shear mixing and reactive extrusion, a higher grafted PLA molar percentage (maximum 62 mol % PLA) was achieved compared to the previous copolymerization methods .…”
Section: Resultsmentioning
confidence: 99%
“…Actually, this study was a continuation of our previous studies presenting processing under a high shear rate to enhance the miscibility between starch and PLA for the fabrication of highly dispersed graft copolymers and their nanocomposites without the addition of any additives and conventional solvents by means of a high‐shear reactor and a twin‐screw extrusion system . The thermal stability, morphologies, and mechanical and permeability properties of the films were studied as a function of the starch–LA ratio and nanoclay content variations.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Stannous octoate can also be used to graft poly( l ‐lactide) on gelatinized starch (water was removed before grafting reaction) with lactide or lactic acid (formation of l ‐lactide in situ in the reaction medium) as the substrate. This grafting reaction was performed under various conditions on gelatinized starch: microwave heating (GP = 62%) , supercritical carbon dioxide medium (GP = 21–52%) , ionic liquid as the solvent (GE = 30%) . In the previous studies, XRD analysis showed that the grafting reaction modified the crystallinity of native starch and polylactide.…”
Section: Grafting From Via Ring Opening Polymerization (Rop)mentioning
confidence: 99%